Effect of ouabain on Na, K-ATPase and electrolyte transport in the dog ileum in vivo. Issue 5 (May 1979) - Read, N W; Krejs, G J; Jones, V E; Fordtran, J S
Abstract : It is currently believed that the rate and direction of sodium transport in the small intestine may be regulated by the activity of Na, K-ATPase in the basolateral cell membrane. We tested this hypothesis by selectively infusing ouabain, a known inhibitor of Na, K-ATPase, into the mesenteric artery supplying a perfused loop of ileum in 18 dogs. Before ouabain infusion there were significant correlations between the activity of Na, K-ATPase and net and lumen to plasma fluxes of sodium and chloride. After ouabain, there was no significant change in sodium and chloride transport, unidirectional fluxes or transmucosal potential difference, despite a 50% reduction in Na, K-ATPase activity. Furthermore, there was no significant correlation between Na, K-ATPase activity and sodium or chloride transport after ouabain. The only statistically significant effect of ouabain infusion was a reduction in the rate of bicarbonate secretion. Thus, the results of our experiments suggest that mucosal Na, K-ATPase is not a rate-limiting step in the absorption of sodium and chloride in the dog ileum, though it may be an important facilitative factor.